Pengaruh Reputasi, Kualitas Informasi dan E-wom Terhadap Minat Beli Pada Situs Jual Beli Online Tokopedia di Kota Malang - Fifi Rusiliyanti; Nur Hidayati; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine the effect of reputation, information quality and e-wom on purchase intention on the online buying and selling site Tokopedia in Malang City. This study uses a quantitative approach. The population in this study were students in Malang City, who were represented by State Universities, Brawijaya University and Private Universities, Islamic University of Malang. The sampling method in this study used non-probability sampling, namely snowball sampling, in this study the sample numbered 96 respondents. While the data analysis used is Multiple Linear Regression with the help of SPSS 25.0. The resulting conclusion is that reputation has a negative and significant effect on purchase intention, quality of information & e-wom has a positive effect on online purchase intention of Tokopedia among students in Malang City. Keywords: Reputation, Quality of Information, E-wom, Purchase Intention